METHODS OF ASSESSING KNOWLEDGE OF THE RUSSIAN LANGUAGE IN PUPILS OF SCHOOLS WITH UZBEK LANGUAGE OF INSTRUCTION (Web of Teachers: Inderscience Research, 2024)
This article discusses the issues of assessing the knowledge of pupils in the Russian language in schools with Uzbek as the language of instruction; the roles of using methods and techniques of new pedagogical technologies in the classroom are determined on the example of the evaluation sheet.